The anomalous legal thought in building an equitable legal theory - Prof. I Made Arya Utama (Indonesia Prime, 2017)
The challenges of current and future Law Theories are not solely derived from within the Law itself, but also from the external about the law's enforceability in society. Therefore, the legal theories are currently experiencing anomalies. Legal Theory currently faced with the need to be able to bring about justice, certainty, order, and the benefits of protecting human rights as well as the sustainability of living creatures and the environment.The method applied in this article is the normative legal research method with the source of legal material from the legislation and related literature. Library study became the technique of collecting the legal material and qualitative analysis applied to the legal material which has been described to produce the conclusion of the problems studied in this article.The legal theory undergoes a shift following the perspective of legal scholars from classical times, modern times, and postmodern thinkers. The Depelovment Law Theory and Progressive Law Theory that grew up in the Postmodern era seeks to free the minds of the status quo, adopt legal ideas that are in line with the needs of the Indonesian people and the state that is moving in the crossroads of modernization. Laws are required to promote conscience implemented through legal products established by competent authorities, just laws, and laws protecting people and the environment.